Room temperature magnetoresistance in an organic spin valve with an aromatic hydrocarbon macrocycle - Kazuya Z. Suzuki (APL Materials, 2017)
Aromatic hydrocarbon macrocycles, which have a conjugated π-electron system, are potentially useful for various organic device applications, although there have been no attempts to apply them to organic spin valves (OSVs). Here, we studied OSVs with [6]cyclo-2,7-naphthylene (CNAP), a type of aromatic hydrocarbon macrocycle. OSV stacking structures of Co/AlOx/CNAP/Ni80Fe20 with different CNAP thicknesses were fabricated, and the transport properties of the OSVs were measured from 300 to 5 K. A magnetoresistance of approximately 1%-2% at 300 K (4%-6% at 5 K) was observed for 15-nm-thick OSVs, showing the potential for organic spintronics based on aromatic hydrocarbon macrocycles.